Association of Tetrahydrocannabinol Content and Price in Herbal Cannabis Products Offered by Dispensaries in California: A Purview of Consumers/Patients - Dobbins, MaryBeth; Rakkar, Mannat; Cunnane, Katharine; Pennypacker, Sarah D.; Wagoner, Kimberly G.; Reboussin, Beth A.; Romero-Sandoval, E. Alfonso (Frontiers in Public Health, 2022)
Background and Aims The U.S. legal cannabis market is saturated with products containing high levels of tetrahydrocannabinol (THC), with no distinction between medical and recreational programs. This omnipresence of potent cannabis products seems to be driven by the recreational realm, where cannabis with the highest THC content is prized. This prevalence of highly potent cannabis is conveyed to medical programs, which places consumers (patients) at higher risk for over consumption and cannabis use disorder. Thus, understanding what factors influence the market that patients face in medical cannabis programs could shed light on the risks of legal cannabis. The supply and demand dynamic of the US for-profit cannabis market could explain the current market composition; therefore, we postulate that a financial gain could influence the perpetuation of the prevalence of high THC products in legal cannabis dispensaries. We investigate whether THC content in popular cannabis products correlates with higher prices and assess whether some attributes (type of product, chemovars, or presence of cannabidiol (CBD) affect the association of THC with price. Methods We focus on the world's largest cannabis market, California. We randomly selected dispensaries across the state, screened for a web presence and product menu, determined the most prevalent product type, and collected THC and CBD concentration, price, and other product attributes. Results We observed that herbal products were more common, they had THC concentrations greater than 10%, and THC concentrations positively correlated with price. This correlation existed in flower and preroll presentations, all chemovar, and independently of the level of CBD. CBD did not correlate with price; however, the presence of CBD diminished the THC and price correlation particularly in products with high THC (>15%). Conclusions Overall, highly potent herbal cannabis products (>15% THC) are the majority of products offered and more expensive regardless of product type or chemovar in California dispensaries, suggesting that a financial gain contributes to the current market composition. Efforts to limit the availability of highly potent THC products and educate consumers about potential harms are needed.